2020
DOI: 10.1038/s41598-020-69317-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of uterine microbiota in postpartum dairy cows with clinical or subclinical endometritis

Abstract: our objectives were to describe and compare the uterine bacterial composition of postpartum Holstein cows diagnosed as healthy (n = 8), subclinical endometritis (SCE; n = 8), or clinical endometritis (CE; n = 5) in the fifth week postpartum. We did metagenomic analyses of 16S rRNA gene sequences from endometrial cytobrush samples at 10, 21, and 35 days in milk (DIM), and endometrial bacterial culture at 35 DIM. Uterine bacterial composition in healthy, SCE, and CE was stable at 10, 21, and 35 DIM. Alpha and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 28 publications
4
71
2
1
Order By: Relevance
“…Although none of the cows in our study had clinical disease, there was variation in the proportions of endometrial PMN. Wang et al [ 5 ] and Pascottini et al [ 6 ] showed that neither the alpha and beta diversities nor the relative abundance of bacteria phyla and genera differed between healthy and SCE cows. However, it was shown that in cows with PVD (or clinical endometritis), there was an increased relative abundance of Trueperella in comparison to healthy or SCE [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although none of the cows in our study had clinical disease, there was variation in the proportions of endometrial PMN. Wang et al [ 5 ] and Pascottini et al [ 6 ] showed that neither the alpha and beta diversities nor the relative abundance of bacteria phyla and genera differed between healthy and SCE cows. However, it was shown that in cows with PVD (or clinical endometritis), there was an increased relative abundance of Trueperella in comparison to healthy or SCE [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For that study, 20 out of 42 Holstein cows received subcutaneous injections of meloxicam (0.5 mg/kg of body weight; Metacam, Boehringer Ingelheim Canada Ltd., Burlington, ON, Canada) once daily on 10, 11, 12 and 13 DIM (the rationale for this meloxicam dosing is described by Pascottini et al [ 14 ]. In a subsequent experiment using 21 cows from the underlying study, we compared the uterine bacterial composition of postpartum cows diagnosed with SCE (absence of mucopurulent vaginal discharge but with ˃ 5% endometrial polymorphonuclear neutrophils (PMN); n = 8), clinical endometritis (mucopurulent or purulent vaginal discharge with ˃ 5% endometrial PMN; n = 5), or healthy (neither SCE nor CE; n = 8) in the fifth week postpartum [ 6 ]. Uterine bacterial composition was not different between healthy and SCE cows, but uterine microbiota differed in cows with clinical endometritis [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative Medicine and Cellular Longevity confirmed the presence of fungal septicemia and Escherichia coli as the main pathogens responsible for endometritis in cattle, often isolated from the uterus [4,28,29]. LPS is an endotoxin found in the outer cell wall of Gram-negative bacteria [30,31]. To assess bacterial contamination in uterine tissue, Gram staining was conducted to examine the status and morphological feature of bacteria in the endometrium of uterine horn (n = 8) diagnosed with endometritis or pyometra.…”
mentioning
confidence: 99%